CircRNA-mediated regulation of cardiovascular disease - Cheng, Ke-yun; Wang, Si-wei; Lan, Tian; Mao, Zhu-jun; Xu, You-yao; Shen, Qing; Zeng, Xi-xi (Frontiers in Cardiovascular Medicine, 2024)
Cardiovascular diseases (CVDs) encompass a range of disorders affecting the heart and blood vessels, such as coronary heart disease, cerebrovascular disease (e.g., stroke), peripheral arterial disease, congenital heart anomalies, deep vein thrombosis, and pulmonary embolism. CVDs are often referred to as the leading cause of mortality worldwide. Recent advancements in deep sequencing have unveiled a plethora of noncoding RNA transcripts, including circular RNAs (circRNAs), which play pivotal roles in the regulation of CVDs. A decade of research has differentiated various circRNAs by their vasculoprotective or deleterious functions, revealing potential therapeutic targets. This review provides an overview of circRNAs and a comprehensive examination of CVDs, the regulatory circRNAs within the vasculature, and the burgeoning research domain dedicated to these noncoding RNAs.